2021
DOI: 10.3389/fcimb.2021.627630
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum Induces TLR- and MyD88-Dependent Signaling in In Vitro Generated Murine Neutrophils

Abstract: Anaplasma phagocytophilum is a tick-transmitted obligate intracellular Gram-negative bacterium that replicates in neutrophils. It elicits febrile disease in humans and in animals. In a mouse model, elimination of A. phagocytophilum required CD4+ T cells, but was independent of IFN-γ and other classical antibacterial effector mechanisms. Further, mice deficient for immune recognition and signaling via Toll-like receptor (TLR) 2, TLR4 or MyD88 were unimpaired in pathogen control. In contrast, animals lacking ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Recently, the link between MyD88-or TRIF-dependent TLRs and inflammation has been explored via in vitro and in vivo approaches. Infected MyD88 −/− , MyD88/ TRIF −/− , and TLR2/3/4/7/9 −/− murine Hoxb8 neutrophils, compared with WT cells, show diminished proinflammatory responses (Nos2 transcripts; TNFα, CCL4, and CCL5 secretion) [98]. Despite differences in inflammation in vitro, no phenotypic differences have been observed in vivo between infected WT C57BL/6 and TRIF −/− mice.…”
Section: Immune Recognitionmentioning
confidence: 91%
See 4 more Smart Citations
“…Recently, the link between MyD88-or TRIF-dependent TLRs and inflammation has been explored via in vitro and in vivo approaches. Infected MyD88 −/− , MyD88/ TRIF −/− , and TLR2/3/4/7/9 −/− murine Hoxb8 neutrophils, compared with WT cells, show diminished proinflammatory responses (Nos2 transcripts; TNFα, CCL4, and CCL5 secretion) [98]. Despite differences in inflammation in vitro, no phenotypic differences have been observed in vivo between infected WT C57BL/6 and TRIF −/− mice.…”
Section: Immune Recognitionmentioning
confidence: 91%
“…The authors observed significantly increased A. phagocytophilum loads in the blood and lungs of NOD2 −/− C57BL/6 mice throughout the course of infection, but both NOD2 −/− and WT mice eventually cleared the bacterium at similar rates [98]. In experiments using Hoxb8 murine neutrophils, no differences in bacterial load or proinflammatory markers have been observed among infected WT, NOD1 −/− , NOD2 −/− , and NLRP3 −/− cells [98]. However, A. phagocytophilum has been shown to activate NLRC4 via a unique mechanism.…”
Section: Immune Recognitionmentioning
confidence: 97%
See 3 more Smart Citations